Computers in today's world - Stair, Ralph M. (Homewood, Ill. : Irwin, 1986)
Provides students with an up-to-date and comprehensive introduction to computers in today's world. Microcomputer Examination Review and Study Guide.
Reference card for BASIC inserted.
Includes index.
kjo 15/01/2019
Loans
Keywords: Computers